Endurance ratios of middle-distance race - Lazareva, E. A.; Stepanova, O. A.; Panova, E. O.; Kochurova, L. A.; Grigorieva, N. S. (Journal of Human Sport & Exercise, 2019)
The paper deals with the ergometric endurance criteria in field-and-track middle-distance race and systematizes the applied training means according to the direction (nature) of the physiological effect. The ergometric analysis of `velocity - time` and `distance - time` dependences, according to the data of the world race records, allows defining the role of the aerobic and anaerobic energy production at particular distances of the field-and-track race. The level of development of the sportsmen`s aerobic and anaerobic capacities affects the manifestation of special endurance in the middle-distance race. The experiment was conducted among field-and-track athletes of high qualification specializing in the middle (800 and 1500 m) distances. The main factor influencing the result in a race is the energy indicators. So, their measurement and estimate serve the main leverage of the training session. The use of predominantly anaerobic exercises during the specialized work-outs significantly improves the runners` special endurance indicators.